Phytochemical-mediated efferocytosis and autophagy in inflammation control - Asma Vafadar; Amir Tajbakhsh; Fatemeh Hosseinpour-Soleimani; Amir Savardshtaki; Mohammad Hashem Hashempur (Cell Death Discovery)
Abstract Efferocytosis, the clearance of apoptotic cells, is a critical process that maintains tissue homeostasis and immune regulation. Defective efferocytosis is linked to the development of chronic inflammatory conditions, including atherosclerosis, neurological disorders, and autoimmune diseases. Moreover, the interplay between autophagy and efferocytosis is crucial for inflammation control, as autophagy enhances the ability of phagocytic cells. Efficient efferocytosis, in turn, regulates autophagic pathways, fostering a balanced cellular environment. Dysregulation of this balance can contribute to the pathogenesis of various disorders. Phytochemicals, bioactive compounds found in plants, have emerged as promising therapeutic agents owing to their diverse pharmacological properties, including antioxidant, anti-inflammatory, and immunomodulatory effects. This review aims to highlight the pivotal role of phytochemicals in enhancing efferocytosis and autophagy and explore their potential in the prevention and treatment of related disorders. This study examines how phytochemicals influence key aspects of efferocytosis, including phagocytic cell activation, macrophage polarization, and autophagy induction. The therapeutic potential of phytochemicals in atherosclerosis and neurological diseases is highlighted, emphasizing their ability to enhance efferocytosis and autophagy and reduce inflammation. This review also discusses innovative approaches, such as nanoformulations and combination therapies to improve the targeting and bioavailability of phytochemicals. Ultimately, this study inspires further research and clinical applications in phytochemical-mediated efferocytosis enhancement for managing chronic inflammatory and autoimmune conditions.